Teripang sebagai Sumber Pangan dan Bioaktif - . Kustiariyah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2007)
Sea cucumber (Holothurians) is one of fisheries commodities which has a high economic value. Generally sea cucumber is traded in the dried form (beche-de-mer). Then these holothurians are consumed as dried gonads (konoko) or dried gut (konowata), either holothurians crispy. Bioactive of sea cucumber, commonly known as holothurin, has drawn attention because of its wide spectrum of biological effects namely antibacterial, antifungal, anticancer or cytotoxic, haemolytic and anti-inflammation.Keywords : anticancer, anti-inflammation, Holothuria, natural products, sea cucumber1)Staf